2019
DOI: 10.5037/jomr.2019.10203
|View full text |Cite
|
Sign up to set email alerts
|

Mouth Cancer Awareness in General Population: Results from Grampian Region of Scotland, United Kingdom

Abstract: Objectives The purpose of this project was to determine the level of mouth cancer awareness and to investigate the associated factors in a United Kingdom (UK) general population sample. Material and Methods Adult Dental Health Survey (2010) was conducted in a sample of 3,353 adult residents in the Grampian region of the UK (adjusted participation rate 58%). Participants completed a questionnaire consisting of questions on oral health, health behaviour, quality of life a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…The self-declared awareness of oral cancer correlated positively with age and no significant differences were found in terms of gender. This is consistent with some studies, 17 while other ones showed deficits in older patients and male respondents. 23 An important observation was that the awareness of risk factors and early signs of the disease correlates positively with the level of education, as shown in previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The self-declared awareness of oral cancer correlated positively with age and no significant differences were found in terms of gender. This is consistent with some studies, 17 while other ones showed deficits in older patients and male respondents. 23 An important observation was that the awareness of risk factors and early signs of the disease correlates positively with the level of education, as shown in previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Over 65% of the respondents in our study had ever heard about oral cancer, which is comparable to the studies from different countries. [15][16][17] The sources of the information were, similarly to the other studies, mainly television, radio and newspapers, but the role of the Internet is gaining significance. [18][19][20] The fact that less than a quarter of respondents mentioned doctors as a source of information about oral cancer is alarming.…”
Section: Discussionmentioning
confidence: 81%
“…In a recent study in the United Kingdom, Kawecki et al, using the deprivation index, indicated lower knowledge of mouth cancer in the most deprived areas (41). These studies are in line with our study.…”
Section: Discussionsupporting
confidence: 93%
“…Age was recorded in date of birth and was categorised into groups of [25][26][27][28][29][30][31][32][33][34][35][35][36][37][38][39][40][41][42][43][44][45], and > 45 years.…”
Section: Covariatesmentioning
confidence: 99%
“…Most of the previous literature and people generally believed that those with a higher education level and higher living standard have higher awareness of oral cancer [25][26][27]. According to the results of this survey, the main factors affecting people's awareness of oral cancer were age, living standards, and oral hygiene habits.…”
Section: Discussionmentioning
confidence: 79%